2016
DOI: 10.1002/ange.201605507
|View full text |Cite
|
Sign up to set email alerts
|

Reagents with a Crystalline Coat

Abstract: Tetrakis(dimethoxyphenyl)adamantane (TDA) readily forms crystalline inclusion complexes with reactive, toxic, or malodorous reagents,such as benzoyl chloride,acetyl chloride,c yclohexyl isocyanide,p hosphorus trichloride,a nd trimethylsilyl chloride.T he crystals are stable and largely free of the problematic properties of the free reagents.W hen exposed to solvents such as DMSO or MeOH, the reagents react, and al arge portion of the TDAp recipitates.T he TDAcoated reagents may lead to as afer way of storing,h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…We opted for a benzene derivative for our first foray into organic solids to be encapsulated in TAA crystals, because a number of benzene derivatives have been found in EnOCs in the past [13][14][15]. Phenol was considered an interesting case, as the molecule crystallizes easily; setting up what may be considered a molecular competition between two readily crystallizing compounds (TAAs usually crystallize within minutes upon cooling of a saturated solution).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We opted for a benzene derivative for our first foray into organic solids to be encapsulated in TAA crystals, because a number of benzene derivatives have been found in EnOCs in the past [13][14][15]. Phenol was considered an interesting case, as the molecule crystallizes easily; setting up what may be considered a molecular competition between two readily crystallizing compounds (TAAs usually crystallize within minutes upon cooling of a saturated solution).…”
Section: Resultsmentioning
confidence: 99%
“…Three tetraaryladamantanes (TAAs) were found to show this behavior as hosts, namely 1,3,5,7-tetrakis(2,4-dimethoxyphenyl)adamantane (TDA), 1,3,5,7-tetrakis(2,4-diethoxyphenyl)adamantane (TEO), and 1,3,5,7-tetrakis(2-bromo-4-methoxyphenyl)adamantane (TBro). The X-ray crystal structures of over 100 EnOCs have been reported thus far [13][14][15][16], including structures with chiral guests that allow for the determination of the absolute [17] or relative configuration [18]. One limitation of the EnOC method was that the guest compound to be encapsulated had to be a liquid, so that it could act as solvent for the TAA, which would rapidly crystallize upon cooling of a hot, saturated solution.…”
Section: Introductionmentioning
confidence: 99%
“…This octaether was originally prepared as an intermediate in the synthesis of branched oligonucleotide hybrids (Singh et al 2011;Schwenger et al 2017), but was studied as a crystalline host when it was found to give solvates with a large number of structurally diverse organic liquids (Schwenger et al 2015). Stable crystalline inclusion complexes with reagents as different in structure and polarity as acetyl chloride, piperidine, cyclohexyl isocyanide and trimethylsilyl chloride were obtained (Schwenger et al 2016). The ethyl derivative 1,3,5,7-tetrakis(2,4-diethoxyphenyl)adamantane (TEO) was then found to accommodate up to 3.5 equivalents of guest molecules in its crystals and to capture and release liquid aromatic hydrocarbons via the gas phase (Alexandre et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the breadth of the effect found for TAA octaethers, we coined the term "encapsulating organic crystals" (EnOCs) for these inclusion compounds (Richert and Krupp 2017). Unlike crystals based on compounds that cannot form tightly packed crystalline arrangements (Tian et al 2009), the host molecules of EnOCs are able to assemble into closely packed crystals with a density typical for organic compounds (Schwenger et al 2016). For example, TDA has been found to crystallize in a solvate-free triclinic system with a density of 1.30 g/cm 3 , whereas some solvates have a lower density, such as the monoclinic form with acetone guest molecules (density 1.28 g/cm 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the outset of our study, 48 crystalline inclusion complexes of tetraaryladamantanes had been found in our laboratories, [18][19][20][21] none of which contained a chiral guest molecule. We chose the structurally diverse analytes of Figure 2 for single-run thermal crystallization experiments with TDA or TBro.…”
mentioning
confidence: 99%